Robust longitudinal multi-cohort results: The development of self-control during adolescence. (October 2020) - Zondervan-Zwijnenburg, M.A.J.; Richards, J.S.; Kevenaar, S.T.; Becht, A.I.; Hoijtink, H.J.A.; Oldehinkel, A.J.; Branje, S.; Meeus, W.; Boomsma, D.I.
Abstract: Longitudinal data from multiple cohorts may be analyzed by Bayesian research synthesis. Here, we illustrate this approach by investigating the development of self-control between age 13 and 19 and the role of sex therein in a multi-cohort, longitudinal design. Three Dutch cohorts supplied data: the Netherlands Twin Register (NTR; N = 21, 079), Research on Adolescent Development and Relationships-Young (RADAR-Y; N = 497), and Tracking Adolescents' Individual Lives Survey (TRAILS; N = 2229). Self-control was assessed by one measure in NTR and RADAR-Y, and three measures in TRAILS. In each cohort, we evaluated evidence for competing informative hypotheses regarding the development of self-control. Subsequently, we aggregated this evidence over cohorts and measures to arrive at a robust conclusion that was supported by all cohorts and measures. We found robust evidence for the hypothesis that on average self-control increases during adolescence (i.e., maturation) and that individuals with lower initial self-control often experience a steeper increase in self-control (i.e., a pattern of recovery). From self-report, boys have higher initial self-control levels at age 13 than girls, whereas parents report higher self-control for girls.